Synthesis and Characterization of Organoheterotrimetallic Dibutyl-[Sn(IV), Ti(IV), Al(III)]-μ-oxoisopropoxide and Its b-Diketonates - K. Sharma, Harish; Singh, Jashmer (Asian Journal of Chemistry, 2014)
Thermal condensation of dibutyl tin diacetate and aluminium isopropoxide in 1:1 molar ratio in refluxing xylene affords [(AcO)Bu2SnOAl(i-OPr)2] which on reaction with titanium isopropoxide in 1:1 molar ratio yields a new organoheterotrimetallic dibutyl [Sn(IV), Ti(IV), Al(III)]-μ-oxoisopropoxide with continuous liberation of isopropyl acetate. The isopropoxy substitution reactions of μ-oxoisopropoxide compound with b-diketones in different molar ratios (1:1-1:2) gives compounds of the type [Bu2SnO2TiAl(i-OPr)5-nLn] (where n is 1-2 and L = acetylacetonate/benzoylacetonate anion). The μ-oxoisopropoxide compound has been characterized by elemental, spectral analysis (IR, 1H, 13C, 119Sn and 27Al NMR) and molecular weight measurement. The b-diketonates of [Bu2SnO2TiAl (i-OPr)5] have been characterized by elemental, liberated isopropanol and spectral analysis (IR, 1H, 13C NMR).